Pemodelan Hubungan Parameter Karakteristik Lalu Lintas pada Jalan Tol Belmera - Lubis, Adina Sari; Muis, Zulkarnain A; Nasution, Triana (Department of Civil Engineering, Diponegoro University, 2016)
Belmera toll road in North Sumatra was the first toll road, links Belawan-Medan-Tanjung Morawa. The aim of this research is to find the relationship model between speed, density and volume on Belmera toll road based on a traffic study. The traffic study which embodies volume study and the speed of vehicles were divided into 5 vehicle classification, into 2 traffic lines (Entrance and Exit Tanjung Morawa’s toll gates), was conducted on Friday and Saturday around the peak hour on each traffic current. The study concluded that Greenberg model is the best approach for traffic current on Belmera toll road. According to Greenberg model we acquire a mathematical equation of the relationship between speed-density, volume-density, and volume-speed of Exit Tanjung Morawa’s toll gates as: S=98,100-6,700LnD, V=98,100D–16,700DLnD, V=355,758Se-0,059S and the Entrance as: S=99,312–17,442LnD, V=99,312D–17,442DLnD, V=297,033 Se-0,057S. Based on the observation and application of Greenberg model, traffic indicator (v/c, flow, density) of both current revealed that the level of service of Belmera toll road is C and it’s a fine traffic performance so far. The speed rate (km/hour) and density (pcu/km) revealed that the acquired rate from the observation is smaller than the application of Greenberg model.